POTENSI LANSKAP DESA PURWODADI SEBAGAI OBJEK DESA WISATA DI KABUPATEN MALANG - Debora Budiyono Budiyono; Nuraini Nuraini; Alfiyah Alfiyah (BUANA SAINS, 2020)
Purwodadi village is one of the village landscapes that has interesting natural and cultural potential to be developed as objects and attractions of toursim village. However the problem in Purwodadi village is not yet identified the potential of the landscape that can be developed into a tourism village object. Village tourism is one of the components between provided, accommodation and supporting facilities provided in the structure of the community with the prevailing order in the village. The purpose of this study was to identify the potential of the Purwodadi village landscape as a tourism village. The method used in the study is focus group discussion (FGD). Based on the identification results show that the village landscape of Purwodadi has 22 types of objects and potential attractions consisting of natural and cultural tourism. Natural potentials that can be developed are beaches, islands, agriculture, and animal husbandry. While the cultural potential consists of the offerings, art, carnival, and historical objects.